Aceh Conflict Resolution, Actions of Non-GAM Acehnese in Peace in Veranda of Mecca Post-MoU. Helsinki - Rukaya Rukaya; Alexius Aan; Sherley Chintya; Nina Ayuni; Okta Putri; Heni Kuswati; Nur Sutari; Hesky Septiawan; Ariya Winandar; Dede Yas Putra; Jagad Aditya Dewantara (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Following several years of world political leadership beset by clashes between nations, the trend lately is to spread invisible turmoil within a nation, such as between ethnic struggles and withdrawal or rebellion. New issues in the globalization cycle are related to issues of basic freedoms, political, monetary and social changes, followed by the development of different struggles. According to social researcher Hugh Miall, "the breakdown of the Soviet Association completed a wide-ranging series of battles in which solitary clashes around the world dominated the global framework, rather than subterranean struggles such as ethnic strife, disobedience and clashes for power in many countries, finally becoming something of a signature" (Miall, 2002: 3) As a result of continuing patriotic clashes, it has resulted in ethnic clashes or national conflicts between regions that want to alienate themselves from the real government, as happened in Indonesia, such as in Papua, Maluku, Aceh, and East Timor which in the end it was discovered how to isolate it from the Unitary State of the Republic of Indonesia.Relating to Aceh, Wahyudi (2005: 2) argues that, the changes that brought an environment of opportunity for individual Acehnese were successfully used by dissident developments to inflame the spirit of independence, so that the situation that occurred was true. -absolutely wild and full of vulnerabilities. Public administration is paralyzed, regulations and instruments are ineffective, the economy is stale, and perhaps the turbulent state is allowed to continue. The issue of disobedience was revitalized in recent improvements in Indonesia, beginning with the raising of the South Maluku Republic (RMS) banner before President Susilo Bambang Yudhoyono, with a gathering of RMS supporters in commemoration of Big Family Day at Merdeka Square in Ambon. The raising of the RMS banner, in addition to the performance of the Cakalele dance on that occasion, the raising of the Morning Star flag in Papua and the tendency for GAM credit to continue to be used in Aceh.